Proceedings of the Annual Conference of the South African Institute of Computer Scientists and Information Technologists 2018
DOI: 10.1145/3278681.3278695
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the antecedents to teaching green information technology (Green IT)

Abstract: There is abundant scientific evidence that the natural environment, on which we are completely dependent for life, is degrading and depleting to the extent that our medium-to longterm well-being and existence is under threat. It is also clear that IT is contributing to this degradation and depletion, which requires that Green IT practices be an imperative. Since Green IT practices are often not common sense, it is vital that these Green IT practices are taught to others, and teachers typically have the skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Todd et al. (2014) and Dlamini and Ramburan (2016) also reported significant variety × soil interactions. Variety N36 with regard to sucrose yield performed better on moderately and poorly draining soils than the other varieties, while N25 performed better on well-draining soils.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Todd et al. (2014) and Dlamini and Ramburan (2016) also reported significant variety × soil interactions. Variety N36 with regard to sucrose yield performed better on moderately and poorly draining soils than the other varieties, while N25 performed better on well-draining soils.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies reported significant variety × season interactions as well (Di Bella et al. , 2009; Dlamini and Ramburan, 2016; Farrag et al. , 2019), emphasizing the importance of selecting varieties for seasonal adaptation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations